Leukocytes and Neutrophil–Lymphocyte Ratio as Indicators of Insulin Resistance in Overweight/Obese School-Children - Rodríguez-Rodríguez, Elena; Salas-González, M. Dolores; Ortega, Rosa M.; López-Sobaler, Ana M. (Frontiers in Nutrition, 2022)
Background and aims: Inflammation in overweight/obesity may condition the development of insulin resistance (IR). New markers of inflammation and systemic inflammation, such as leukocyte and platelet counts, the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR), could be used as indicators of IR. The aim of the present study was to investigate the relationship between these markers and IR in overweight/obese children. Materials and methods: A total of 1035 schoolchildren were studied (398 overweight/obese). Anthropometric, hematological and biochemical measurements were collected. Inflammation was considered to be present when the values of leukocytes, platelets, NLR, PLR and MLR were greater than p75 for each sex. IR was defined as HOMA-IR greater than 3.16. Results: In overweight/obese schoolchildren, leukocytes were higher in both boys and girls, and platelets and NLR were higher in boys with IR than in boys with insulin sensitivity. An association between leucocytes and NLR values (≥p75) and IR was found in the entire population [2.687 (1.208-5.977); p=0.015 and 2.491 (1.104-5.620); p=0.028, respectively] and in boys [7.430 (1.462-37.754); p=0.016 and 6.565 (1.226-35.165); p=0.028, respectively]. Conclusion: Elevated white blood cell values and elevated NLR in overweight/obese children, and particularly in boys, could be indicators of the presence of IR in these subjects and should be considered when predicting possible complications, such as type II diabetes mellitus.